2009
DOI: 10.1111/j.1445-6664.2009.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased foliar activity of clodinafop‐propargyl and/or tribenuron‐methyl by surfactants and their synergistic action on wild oat (Avena ludoviciana) and wild mustard (Sinapis arvensis)

Abstract: Increased foliar activity of clodinafop-propargyl and/or tribenuron-methyl by surfactants and theirsynergistic action on wild oat (Avena ludoviciana) and wild mustard (Sinapis arvensis) wbm_353 292..299Surfactants can improve postemergence herbicide efficacy and reduce the amount of herbicide required to obtain weed control.The effect of surfactants on the efficacy of herbicides is complicated and depends on the interaction among the plant, surfactant, and herbicide.The effects of surfactants on the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…These results are also in agreement with those by Aliverdi et al (2009). They reported that the tank-mix application of tribenuron-methyl and adjuvants have a synergistic effect to control weeds in wheat.…”
Section: Effect Of Herbicides With or Without Adjuvants On Weed Densisupporting
confidence: 83%
“…These results are also in agreement with those by Aliverdi et al (2009). They reported that the tank-mix application of tribenuron-methyl and adjuvants have a synergistic effect to control weeds in wheat.…”
Section: Effect Of Herbicides With or Without Adjuvants On Weed Densisupporting
confidence: 83%
“…Aliverdi et al (2009) 1). It is well established by experimental evidence that surfactants containing lower ethylene oxide units were more effective than surfactants containing higher ethylene oxide units in decreasing the static surface tension of spray solutions (Shah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The static surface tension of aqueous solution of cationic and nonionic surfactant alone was measured as reported by Aliverdi et al (2009). The herbicides Nos.…”
Section: Methodsmentioning
confidence: 99%
“…Previous papers have reported that environmental conditions affect the activity of tribenuron methyl and other sulfonylurea herbicides (Kudsk et al 1990, Olson et al 2000. It has also been reported that the impact of climatic factors depends on weed species and can be modified in tank mix with adjuvants (Mathiassen & Kudsk 2002, Bunting et al 2004, Stagnari et al 2006, Aliverdi et al 2009, Pannacci et al 2010. Adjuvants can improve herbicide efficacy because they enhance herbicide adhesion to the leaf surface, decrease the surface tension, prolong the droplet drying period and, therefore, allow more of the active ingredient to penetrate into the plant (Davies & Caseley 2001, Harbour et al 2003, Aliverdi et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the impact of climatic factors depends on weed species and can be modified in tank mix with adjuvants (Mathiassen & Kudsk 2002, Bunting et al 2004, Stagnari et al 2006, Aliverdi et al 2009, Pannacci et al 2010. Adjuvants can improve herbicide efficacy because they enhance herbicide adhesion to the leaf surface, decrease the surface tension, prolong the droplet drying period and, therefore, allow more of the active ingredient to penetrate into the plant (Davies & Caseley 2001, Harbour et al 2003, Aliverdi et al 2009). Adding a surfactant to the spray solution reduces the risk of herbicide failures under adverse soil-climate (Kudsk & Mathiassen 2007).…”
Section: Introductionmentioning
confidence: 99%